POST TSUNAMI IMPACT ON HYPERTENSION AND DIABETES MELLITUS CASES IN PANDEGLANG DISTRICT, BANTEN, INDONESIA - Mugi Wahidin; Fiona Kong; Hadi Safaat (Universitas Airlangga, 2020)
Background: Pandeglang, a district in Banten province, Indonesia, was the worst affected area of the Sunda Strait tsunami which occurred on 22nd December, 2018. Aside from threats of communicable disease outbreaks, the district faced the challenges of managing non-communicable diseases (NCD) in the community. Purpose: The aim of the study is to describe the post tsunami impact on cases of hypertension and diabetes mellitus and the expected one-year projections of these diseases in the district of Pandeglang, Banten. Methods: In January 2019, we collected primary data from Pandeglang District Health Office (DHO) and 15 Public Health Centres (PHCs) that were heavily affected by the tsunami. Surveillance officers were also interviewed for their subjective opinions on disease projections in both the DHO and PHCs. Aggregated data of cases presenting to the PHCs for assistance were analysed in relation to the post tsunami period. The diseases of interest included hypertension and diabetes mellitus. Results: Reported cases of hypertension and diabetes mellitus increased a few days after the tsunami. For hypertension, the cases spiked on the 5th and 8th days, but for diabetes mellitus the spike came much later. Average cases of hypertension and diabetes mellitus per PHC were 62 and 3, respectively. At district and PHC level, hypertension and diabetes mellitus were considered as minor contributing factors to the morbidity and mortality in the affected communities. The projection of these diseases was optimistic after the first month. Conclusion: It can be concluded that the volume of cases with hypertension and diabetes in the district of Pandeglang tended to be in the first few weeks post tsunami These diseases are projected to lessen in the second month after the disaster due to the recovery of local health services.